Topological protection versus degree of entanglement of two-photon light in photonic topological insulators - Konrad Tschernig (Nature Portfolio, 2021)
Topological protection of entangled states is a promising avenue for photonic quantum technologies. Here, Tschernig et al. theoretically analyse the impact of disorder on topological protection of entangled two-photon states in periodic and aperiodic topological insulator lattices.